A mixed method study of airline brand equity - Nakaprasit, Ayudh (Cranfield University, 2012)
This research investigates airline brand equity in a sequential, mixed method study. The initial, exploratory study undertaken with the focus groups identified relevant issues that influence airline brand equity. The secondary associations of airline brands are often related to the airlines’ country of origin and culture or the intangible cues that are used in airline advertisements. These intangible cues and secondary associations play an important role in triggering airline brand awareness and the unique brand value proposition of each airline. The questionnaire-based study shows that the structure of airline brand equity is comprised of three factors. The first factor highlights the importance of airlines being able to provide suitable and innovative products and consistently good service. The second factor is a reflection of the first factor, i.e. airlines that can deliver both suitable tangible products and good services will be able to establish a large base of loyal customers. The third factor highlights the importance of establishing brand awareness. Based on the structure of airline brand equity that was found, there are four clusters of airline passengers with similar airline brand perceptions, namely: ‘Loyal customers’; ‘Asking for consistency customers’; ‘Hard to please customers’; and ‘Difficult to talk to customers’. The determinant attribute analysis shows that the determinant for the choice of airline brand is different. Each airline is different in its branding, products and service strategies. This suggests that the ways in which each airline brand can meet the needs of each group of airline passengers will also be different. This research demonstrates that the structure of airline brand equity for fullservice and low-cost carrier brands is different. For full-service carrier brands, it is the delivery of suitable tangible products and services that encourages loyalty. In contrast, when price is the most influential determinant attribute, it is the low-cost carrier brands’ resources and ability to offer consistently low fares that helps them to establish a large base of repeat customers.